Formulation and Characterization Transdermal Patches of Meloxicam - M, Suhaitamy; H, Bangun; P.A.Z, Hasibuan (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: Meloxicam is a non-steroidal anti-inflammatory drug (NSAID), an enolic acid derivative that inhibits the cyclooxygenase-2 (COX-2) enzyme.and is usually used by the oral route in the treatment of a wide variety of rheumatic diseases, including rheumatoid arthritis (RA), osteoarthritis, low back pain and various other joint diseases. However, when given, meloxicam is given orally, causing gastrointestinal side effects such as bleeding, gastric ulcers, nausea and vomiting, which can occur at any time when given orally. Methods: Transdermal patches of meloxicam were made with a mixture of hydroxypropyl methylcellulose and polyvinylpyrrolidone with various concentrations of enhancers (propylene glycol), that were (F1 10%), (F2 20%), and (F3 30%). Transdermal patches of meloxicam are prepared using the solvent evaporation method. The making of transdermal patches meloxicam was evaluated for various parameters, was evaluated physchochemical, organoleptic, thickness, weight uniformity, folding resistance, moisture content, and swelling properties. Results: Transdermal patches of meloxicam from three formulas were yellow patches, odorless, slightly wet and flat surface, thickness between 0.0225±0.0005 to 0.0249±0.0001 cm, weight uniformity between 322.56±2.22 to 368.98±1.42 mg, folding resistance between 355.00±3.00 to 386.33±1.53, moisture content between 2.889±0.003 to 3.654±0.009% and swelling between 2.86 up to 3.24%. Conclusion: The results of the study concluded that the meloxicam transdermal patch preparation had good characteristics, the results obtained met the requirements of a transdermal patch, namely having a flat and slightly wet shape and surface, having uniform weight, thickness, folding resistance and having good patch development power.